Diverse mutants of HIV RRE IIB recognize wild‐type Rev ARM or Rev ARM R35G‐N40V. Issue 12 (30th June 2015) - Abdallah, Emane Y.; Smith, Colin A.
Abstract : The binding of human immunodeficiency virus Rev protein via its arginine‐rich motif (ARM) to an internal loop in the Rev‐response element region IIB (RRE IIB) is necessary for viral replication. Many variant RNAs and ARMs that bind Rev and RRE IIB have been found. Despite the essential role of Rev asparagine 40 in recognition, the Rev ARM double‐mutant R35G‐N40V functions well in a Rev–RRE IIB reporter assay, indicating R35G‐N40V uses a distinct recognition strategy. To examine how RRE IIB may evolve specificity to wild‐type Rev ARM and R35G‐N40V, 10 RRE IIB libraries, each completely randomized in overlapping regions, were screened with wild‐type Rev ARM and R35G‐N40V using a reporter system based on bacteriophage λ N antitermination. Consistent with previous studies, a core element of RRE IIB did not vary, and substitutions occurred at conserved residues only in the presence of other substitutions. Notably, the groove‐widening, non‐canonical base‐pair G48:G71 was mutable to U48:G71 without strong loss of binding to wild‐type Rev ARM, suggesting U48:G71 performs the same role by adopting the nearly isosteric, reverse wobble base pair. Originating from RRE IIB, as few as one or two substitutions are sufficient to confer specificity to wild‐type Rev or Rev R35G‐N40. The diversity of RRE IIB mutants that maintain binding to wild‐type Rev ARM and R35G‐N40V supports neutral theories of evolution and illustrates paths by which viral RNA–protein interactions can evolve new specificities. Rev–RRE offers an excellent model with which to study the fine structure of how specificity evolves. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Rev‐response element region IIB (RRE IIB) libraries randomized in three base‐pair blocks were screened with the arginine‐rich motif of Rev and its mutant R35G‐N40V that uses a distinct recognition strategy. From RRE IIB, as few as one or two substitutions are sufficient to confer specificity to Rev ARM or R35G‐N40V, supporting neutral theories of evolution and illustrating the paths by which RNA–protein interactions can evolve new specificities.